Deskripsi Miskonsepsi IPA Peserta Didik Kelas VII pada Materi Lapisan Bumi dengan Menggunakan Three-Tier Diagnostic Test - Erni Yuliana R; Nurhayani H. Muhiddin; Ramlawati Ramlawati (Celebes Science Education, 2026)
This study aims to determine the description of science misconceptions using the Three Tier Diagnostic Test in class VII students of SMPN 3 Pattalassang. This research is a descriptive study that uses a quantitative descriptive approach. Quantitative descriptive research design intended to describe the misconceptions of students on the science questions given. The study population was 108 students from 4 classes. Determination of the number of samples using saturated samples where all members of the population will be used as research samples. The research instrument used is a three tier diagnostic test of 17 items that have been validated by content and items. The data collection technique in this study was a written test of the three tier diagnostic test. The data were analyzed by descriptive statistical analysis. Based on the results of data analysis, it is known that misconceptions occur in all concepts in the material of the earth's layers with the percentage of misconceptions of students on the concept of the constituents of the atmosphere by 78.72% (high); the relationship between altitude, air pressure and the number of air molecules by 71.12% (high); characteristics of the troposphere layer by 74.08% (high); characteristics of the stratosphere layer by 68.53% (high); characteristics of the mesosphere layer by 74.08% (high); characteristics of the thermosphere layer by 75.93% (high); characteristics of the exosphere layer by 85.19% (high); characteristics of the lithosphere layer by 64.82% (high); causes of earthquakes by 67.59% (high); causes of volcano formation by 60.19% (high), and characteristics of the hydrosphere by 65.74% (high).